2002
DOI: 10.1007/s00104-002-0430-8
|View full text |Cite
|
Sign up to set email alerts
|

Infizierte Tierbissverletzungen an den Extremitäten

Abstract: The appearance of animal bite injuries varies in regard to location and extent. Injuries with puncture wounds involving the extremities carry great risk of infection. Managing the complications often requires substantial medical treatment and increased costs. The aim of this study is the evaluation of the course of disease, medical care, and treatment costs in patients with infected bite injuries. In the year 2000, 16 patients were treated for infection after bite injuries of the extremities. Fourteen patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(31 reference statements)
0
1
0
1
Order By: Relevance
“…Zur Spülung können Knopfkanülen
Knopfkanülen
oder Katheter
Katheter
verwendet werden, mit deren Hilfe die Wunde entlang des Bisskanals bis in die Tiefe gespült wird ( Cave : Keimverschleppung). Die Hochdruckspülung („jet lavage“) ist nicht zu empfehlen, da sie eine Verbreitung der Infektionserreger in die Gewebetiefe verursachen wird [ 42 , 43 , 44 ]. Als Spüllösung wird physiologische Kochsalzlösung
physiologische Kochsalzlösung
oder Ringer-Lösung
Ringer-Lösung
empfohlen.…”
Section: Therapieunclassified
“…Zur Spülung können Knopfkanülen
Knopfkanülen
oder Katheter
Katheter
verwendet werden, mit deren Hilfe die Wunde entlang des Bisskanals bis in die Tiefe gespült wird ( Cave : Keimverschleppung). Die Hochdruckspülung („jet lavage“) ist nicht zu empfehlen, da sie eine Verbreitung der Infektionserreger in die Gewebetiefe verursachen wird [ 42 , 43 , 44 ]. Als Spüllösung wird physiologische Kochsalzlösung
physiologische Kochsalzlösung
oder Ringer-Lösung
Ringer-Lösung
empfohlen.…”
Section: Therapieunclassified
“…Some studies have shown a gross difference between awareness and actual practice in management of animal bites [2]. In a study about cost of treating the infections caused by animal bites, it has been shown that the average treatment costs for animal bite infections exceeded 6,100 Euros per case for the health insurance companies [3]. In the countries of the Eastern Mediterranean Region of the World Health Organization (WHO), rabies has been recognized as an important health problem [4].…”
Section: Introductionmentioning
confidence: 99%